Position of Laws Using The Omnibus Method (Review of Article 97A of The Law on The Establishment of Laws and Regulations) - Ihsan Badruni Nasution; Wicipto Setiadi; Taufiqurrohman Syahuri (CV. Syntax Corporation Indonesia, 2024)
This paper aims to determine the legal position of laws that use the omnibus method in the system of laws and regulations in Indonesia. The focus of the research focused on the legal position of laws using the omnibus method in terms of the provisions of Article 97A of the Law on the Establishment of Laws and Regulations. Using the normative juridical method through literature study, this paper concludes that with the characteristics of laws that use the omnibus method based on the regulations in Article 97A of the Law on the Establishment of Laws and Regulations, these provisions result in inconsistencies in norms with the provisions of the hierarchy of laws and regulations regulated by Article 7 paragraph (1) and paragraph (2), provision number 223 Annex II Law on the Establishment of Laws and Regulations, as well as deviating the principle of legal preverence, namely the principle of lex posterior derogate legi priori. The vagueness and inconsistency in the formulation of Article 97A norms results in legal uncertainty, thus contradicting the guarantee of legal certainty as mandated by Article 28D paragraph (1) of the NRI Constitution of 1945.